THE EFFECT OF COMPENSATION, WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE - Muhammad Taufik Lesmana; Muhammad Arif; Muhammad Irfan Barus (CERED Indonesia Institute, 2021)
The goal to be achieved in this study is to analyze and determine the effect of the Current Ratio variable on the The purpose of this study was to determine the effect of compensation on employee performance at PT Gracia Pharmindo Medan City. To determine the effect of the work environment on employee performance at PT Gracia Pharmindo Medan City. To determine the effect of Work Discipline on employee performance at PT Gracia Pharmindo Medan City. To determine the effect of compensation, work environment and work discipline on employee performance at PT Gracia Pharmindo Medan City. The approach in this study is an associative approach. The associative approach is an approach where to find out that there is a relationship or influence between the two variables (the independent variable and the dependent variable). Based on the results of the study, it can be concluded that there is a significant effect of compensation on employee performance at PT Gracia Pharmindo Medan City. There is a significant effect of the work environment on employee performance at PT Gracia Pharmindo Medan City. There is a significant influence of Work Discipline on employee performance at PT Gracia Pharmindo Medan City. Simultaneously there is a significant influence between Compensation, Work Environment and Work Discipline on employee performance at PT Gracia Pharmindo Medan City.